2012
DOI: 10.1002/pip.2257
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal power fluctuations of amorphous silicon thin-film solar modules: distinguishing between different contributions

Abstract: Several works report on seasonal fluctuations of power production of amorphous silicon (a-Si). These oscillations are due to two overlapping phenomena (i) spectral and (ii) the Staebler-Wronski effects. It is hence difficult to assess-for a given location and climatic conditions-which one has the largest impact. By means of a straightforward approach based on two sets of singlejunction a-Si photovoltaic modules (stored indoors/exposed outdoors) and on two different I-V measurement set-ups (indoor and outdoor),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…In addition, as is well known and as previously introduced, the spectral composition of the incident solar radiation has a great influence on the seasonal variation of the PR, with particular reference to the products with a layer of amorphous silicon (Virtuani and Fanni, 2014;Gottschalg et al, 2003). Amorphous silicon, in fact, has a narrow spectral response (250-800 nm) and thus is more sensible to the blue components of the spectrum, in comparison with the spectrum response of c-Si (350-1200 nm).…”
Section: Influence Of Climatic Parameters On Energy Performancementioning
confidence: 96%
“…In addition, as is well known and as previously introduced, the spectral composition of the incident solar radiation has a great influence on the seasonal variation of the PR, with particular reference to the products with a layer of amorphous silicon (Virtuani and Fanni, 2014;Gottschalg et al, 2003). Amorphous silicon, in fact, has a narrow spectral response (250-800 nm) and thus is more sensible to the blue components of the spectrum, in comparison with the spectrum response of c-Si (350-1200 nm).…”
Section: Influence Of Climatic Parameters On Energy Performancementioning
confidence: 96%
“…Second it is at temperatures measured as operation temperatures in the field. As it has been observed as a seasonal effect seen in building integrated a-Si technologies, where the power of the PV modules improves during summer and decreases during winter season [21]. Therefore, it was interesting to use outdoor operating temperatures of PV modules in dark to observe the effect of low temperature on the recovery of power.…”
Section: Annealingmentioning
confidence: 99%
“…According to previous studies, the performance of the electricity generation of the PV system was enhanced in the order of the dual-axis tracker type, single-axis tracker type, and fixed type [19][20][21][22]. To improve the performance of the electricity generation of the SPSB, the application of the tracker is required.…”
Section: Tracker Types Installed In Prototype Models Of the Spsbmentioning
confidence: 99%
“…Lazaroiu et al [19], Cruz-Peragón et al [20], and Virtuani and Fanni [21], Heslop and Macgill [22], Mousazadeh et al [23], and Dolara and Mussetta [24] performed comparative analyses on the electricity generation of the PV system according to the tracker type. In these previous studies, the performance of the electricity generation on the PV panel was found to be carried out in the order of the dual tracker, single tracker, and fixed type.…”
Section: Introductionmentioning
confidence: 99%